Qur'anic Therapy: The Impact of Qur'an Recitation on Inner Peace and Mental Health - Diva Datul Isma; Salami Mahmud; Ida Meutiawati (Ameena Journal, 2026)
Indonesia is currently facing a significant mental health crisis, marked by increasing rates of emotional disorders, anxiety, stress, and depression. In addition to medical and social approaches, spiritual dimensions offer an alternative solution to support psychological well-being. This study aims to examine the role of Qur’anic Therapy as a spiritual intervention in fostering inner peace and improving mental health. The research employed a qualitative descriptive approach using a library research method. Data were collected through an analysis of the Qur'an, hadith, scientific journals, books, and relevant previous studies. The findings indicate that the Qur'an serves as syifa’ (healing), providing therapeutic effects on both psychological and spiritual dimensions. Forms of Qur’anic therapy include regular recitation of the Qur'an, listening to murottal, contemplation (tadabbur) of Qur'anic verses, remembrance (dhikr) and supplication based on Qur'anic teachings, as well as ruqyah syar’iyyah. These practices contribute to reducing stress, anxiety, and emotional disturbances by promoting relaxation, stimulating endorphin production, lowering cortisol levels, and strengthening spiritual connection with Allah SWT. Furthermore, interaction with the Qur'an enhances emotional resilience, optimism, self-control, and psychological stability. Therefore, Qur’anic Therapy can be considered a holistic and integrative approach that combines spiritual, psychological, and neurological dimensions, making it a strategic complementary intervention for mental health care in contemporary Indonesian society.